Re-Defining the Villain in A Song of Ice and Fire from the Aspect of Totemism - Öztürk, Emrah (2020)
The confrontation between good and evil is one of the essential aspects of the fantasy genre. In George R.R. Martin’s epic fantasy novel series A Song of Ice and Fire (ASOIAF, 1996-2011), he approaches this conception from a critical point of view. Whilst Martin creates deep and challenging characters in his novels, he introduces the White Walkers to the audience as almost one-dimensional, classic antagonists. It can therefore be questioned whether this contradicts his approach towards the medieval ethos. In order to answer this question, I will approach the narration from the aspect of totemism, and will use totemic signs and values for my analysis. Firstly, I will establish a relationship between totemism and the Old Gods. Conceptions such as ‘sacred totem animal’, ‘totem as an emblem’, ‘restriction of incestuous intercourse’, and ‘spirits’ will be useful for comprehending the Old Gods. Furthermore, I will try to analyze the narration with the elements of totemism. Lastly, in the light of this examination, I will try to explain what theWhite Walkers represent within the narration.
Keywords: A Song of Ice and Fire; George R.R. Martin; Fantasy; Religion; Totemism; white walkers